CURRENT STATUS OF MANAGEMENT OF LATENT TUBERCULOSIS TREATMENT IN THE COMMUNITY: A CASE STUDY IN YEN DUNG WARD AND TAN AN WARD, BAC NINH PROVINCE IN 2025 (Vietnam Journal of Community Medicine, 2026)
Abstract: Managing latent tuberculosis (LTA) treatment is one of the key strategies to achieve the goal of ending tuberculosis in Vietnam by 2035.Objectives and Methods: This study aims to analyze the current state of LTA treatment management in Yen Dung and Tan An wards, Bac Ninh province in 2025 using a descriptive cross-sectional method combining qualitative and quantitative analysis.Results: the number of LTA-positive cases detected in the first six months of 2025 increased by 58% compared to 2024, and the treatment completion rate reached a high level of 92.4%. However, communication efforts remain limited, with a low participation rate in community talks (an average of 18-20 people/session) and 100% of health stations still managing data using paper records, without applying information technology.Recommendations: The study highlights the need for digitalization of management and innovation in communication methods to sustainably maintain treatment outcomes.
Keywords: Latent tuberculosis, Treatment management, Primary healthcare, Bac Ninh.